Improvement of Student Activity and Learning Achievement in Math through Cooperative Learning of Team Game Tournament - Sularti, Sularti (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The aim of this study is to determine whether the application of the TGT (Team Game Tournament) cooperative learning model can increase the activeness and mathematics learning outcomes of class XI TKJ A students of SMKN 1 Pleret. This type of research is classroom action research (PTK). This research was conducted with collaborators who are colleagues. Class XI TKJ A students as research subjects totaled 34 people. This research was conducted in 2 cycles, the first cycle with compound statement material, namely conjunction, disjunction, implication and biimplication. While the second cycle with inverse, conversion, and contraposition materials. The instruments used include observation sheets and test sheets. Data collection was carried out by observation, documentation, field notes and tests. The data analysis technique used is descriptive quantitative data analysis. The results showed that the TGT cooperative learning process which consisted of 5 stages applied to mathematics subjects could increase students’ learning activity and mathematics outcomes. The percentage of student activeness before being given action was only 50%, in the first cycle there was an increase to 70.59% and in the second cycle it increased to 83.95%. From the learning outcomes test, it was found that the number of students who completed before being given the action was only 17.65% in the first cycle, an increase to 29.41% and an increase to 50% in the second cycle.